Avaliação da importância da unidade de conservação na preservação da diversidade de Chironomidae (Insecta: Diptera) no córrego Vargem Limpa, Bauru, Estado de Sáo Paulo - Silva, Fabio Laurindo da; Moreira, Diana Calcidoni; Ruiz, Sonia Silveira; Bochini, Gabriel Lucas (Universidade Estadual de Maringa, 2007)
This study evaluated the water quality of the Vargem Limpa stream and tested the hypothesis that protected stretches of the aquatic system, located within a conservation unit, favor the preservation of the diversity of Chironomidae (Insecta: Diptera). Samplings were conducted in four stations, where some physical and chemical variables were measured. The results obtained by the study indicated the predominance of genera associated with arenaceous substrata, and that the stretches protected by the conservation unit presented better environmental conditions, with better-preserved Chironomidae diversity, demonstrating the importance of these areas in maintaining the diversity of Chironomidae.
Assessment of importance of the conservation unit in the preservation of Chironomidae (Insecta: Diptera) diversity in the Vargem Limpa stream, Bauru, São Paulo State
Keywords: Chironomidae; Conservation unit; Diversity; biodiversity; Brazil; environmental factor; genetic conservation; hypothesis; nonhuman; physical chemistry; stream (river); water quality; Diptera; Insecta